1988
DOI: 10.1007/bf00437921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aflatoxin B1 on the delayed type hypersensitivity and phagocytic activity of reticuloendothelial system in chickens

Abstract: Efforts were made to see the effect of feeding aflatoxin B1 at 0.3 ppm level on various aspects of the immune system in chickens. The birds were fed aflatoxin B1 (AFB1) mixed ration from 0 to 6 weeks of age and thereafter normal feed was given up to 12 weeks of age. The delayed type hypersensitivity reaction of these birds was assessed by contact sensitivity to Dinitrofluorobenzene. The dietary AFB1 significantly suppressed the cell mediated immune response at all the three periods tested (30, 45 and 60 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Among the various types of AF, aflatoxin B 1 (AFB 1 ) is an established hepatocarcinogen that causes liver lesions in both mammals and birds (Wogan, 1973). Several experimental studies have shown that AFB 1 is also immunotoxic in both avian and mammalian hosts (Giambrone et al, 1978;Kadian et al, 1988;Otim et al, 2005). The concept that feeding mycotoxincontaminated diets to dams adversely affects the immune system of developing embryos (Potchinsky and Bloom, 1993;Todd and Bloom, 1980) was strengthened by findings of Qureshi et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of AF, aflatoxin B 1 (AFB 1 ) is an established hepatocarcinogen that causes liver lesions in both mammals and birds (Wogan, 1973). Several experimental studies have shown that AFB 1 is also immunotoxic in both avian and mammalian hosts (Giambrone et al, 1978;Kadian et al, 1988;Otim et al, 2005). The concept that feeding mycotoxincontaminated diets to dams adversely affects the immune system of developing embryos (Potchinsky and Bloom, 1993;Todd and Bloom, 1980) was strengthened by findings of Qureshi et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although AFB 1 biotransformation in mammals is relatively well understood, studies in poultry are still needed (Savlík et al, 2007). Adverse health effects have been reported in turkeys (Quist et al, 2000;Klein et al, 2002;Rauber et al, 2007), quail (Oliveira et al, 2002), chickens (Kadian et al, 1988), and ducks (Barraud et al, 1999). However, large differences in the response of poultry species to AFB 1 have been noted (Leeson et al, 1995) and the biochemical basis for these differences has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These results might be due to the reduction of lymphocyte production in lymphoid organs like spleen, thymus and bursa and bone marrow which cause immunosuppressive effect of T-2 toxin in chickens. Similarly, reduction in delayed type hypersensitivity reaction of chicks by aflatoxin [20] reported. A significant increase in skin thickness and moderate gross lesion were observed in birds fed with glucomannan and the toxin.…”
Section: Discussionmentioning
confidence: 91%